Differential plasticity of extensor and flexor motor cortex representations following visuomotor adaptation - Quinn, L.; Miljevic, A.; Rurak, B.; Marinovic, Welber; Vallence, A. (Springer, 2018)
Representations within the primary motor cortex (M1) are capable of rapid functional changes following motor learning, known as use-dependent plasticity. GABAergic inhibition plays a role in use-dependent plasticity. Evidence suggests a different capacity for plasticity of distal and proximal upper limb muscle representations. However, it is unclear whether the motor cortical representations of forearm flexor and extensor muscles also have different capacities for plasticity. The current study used transcranial magnetic stimulation to investigate motor cortex excitability and inhibition of forearm flexor and extensor representations before and after performance of a visuomotor adaptation task that primarily targeted flexors and extensors separately. There was a decrease in extensor and flexor motor-evoked potential (MEP) amplitude after performing the extensor adaptation, but no change in flexor and extensor MEP amplitude after performing the flexor adaptation. There was also a decrease in motor cortical inhibition in the extensor following extensor adaptation, but no change in motor cortical inhibition in the flexor muscle following flexor adaptation or either of the non-prime mover muscles. Findings suggest that the forearm extensor motor cortical representation exhibits plastic change following adaptive motor learning, and broadly support the distinct neural control of forearm flexor and extensor muscles.